FAKTOR RESIKO YANG MEMPENGARUHI KEJADIAN STROKE PADA PASIEN USIA PERTENGAHAN (45-60 TAHUN) DI RUANG KRISSAN RSUD BANGIL KABUPATEN PASURUAN - Moh Adib Mabruri; Lucia Retnowati; Lingling Marinda Palupi (Poltekkes Kemenkes Malang, 2019)
Stroke is one of the serious health problems because of the high mortality rate and its impact which can cause disability. Many risk factors can cause stroke, consisting of risk factors that can be changed and cannot be changed. Knowledge of stroke risk factors is needed to form effective prevention methods. The purpose of this study was to find out about the risk factors associated with the incidence of stroke in middle-aged patients in the Krissan room in Bangil Hospital, Pasuruan Regency. This research uses correlation analytic design with case control design. The sample size was 34 respondents with purposive sampling technique. Data analysis using Chi Square test. The results showed an association between risk factors for hypertension, p value is 0.003, diabetes mellitus, p value is 0.040, and no association between age risk factors, p value is 0.301, gender, p value is 0.590, history family, p value is 0.072, cholesterol, p value is 0.427, smoking, p value is 0.433, obesity, p value is 0.115, alcohol, p value is 0.821 and heart disease, p value is 0.104 with incidence stroke. Research on risk factors that affect the incidence of stroke in middle-aged patients is expected to be a guideline for maintaining a healthy lifestyle in the community. Keywords: Stroke, Modifiable Risk Factors, Risk Factors Cannot Be Modifiable.